2011
DOI: 10.5194/acp-11-8809-2011
|View full text |Cite
|
Sign up to set email alerts
|

High concentrations of coarse particles emitted from a cattle feeding operation

Abstract: Abstract. Housing roughly 10 million head of cattle in the United States alone, open air cattle feedlots represent a significant but poorly constrained source of atmospheric particles. Here we present a comprehensive characterization of physical and chemical properties of particles emitted from a large representative cattle feedlot in the Southwest United States. In the summer of 2008, measurements and samplings were conducted at the upwind and downwind edges of the facility. A series of far-field measurements… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 48 publications
2
28
0
1
Order By: Relevance
“…Techniques for measuring Raman spectra (RS) of atmospheric aerosol particles and the use of RS for particle characterization continue to be developed (Deboudt et al 2010;Hiranuma et al 2011;Ivleva et al 2007;Ivleva, Niessner, and Panne 2005;Rosasco, Etz, and Cassatt 1975;Rosen and Novakov 1977), and include high-throughput techniques and automated analysis methods (Craig, Bondy, and Ault 2017;Doughty and Hill 2017). Peaks in RS indicate the vibrational frequency modes of molecules.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…Techniques for measuring Raman spectra (RS) of atmospheric aerosol particles and the use of RS for particle characterization continue to be developed (Deboudt et al 2010;Hiranuma et al 2011;Ivleva et al 2007;Ivleva, Niessner, and Panne 2005;Rosasco, Etz, and Cassatt 1975;Rosen and Novakov 1977), and include high-throughput techniques and automated analysis methods (Craig, Bondy, and Ault 2017;Doughty and Hill 2017). Peaks in RS indicate the vibrational frequency modes of molecules.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…3a and c, is typically due to the presence of complex organic matter with conjugate double bounds, biological material, diesel soot, black and brown carbon, or humic-like substances (Escribano et al, 2001;Sadezky et al, 2005;Ivleva et al, 2007). Therefore, we refer to this broad peak as black or brown carbon (BBC) (Hiranuma et al, 2011). Other than peaks assigned to the specific components mentioned here, spectra showing strong fluorescence in the measured range, as shown in Fig.…”
Section: Individual Particle Analysesmentioning
confidence: 99%
“…Particulate matter (PM) collected downwind from cattle feeding yards has been shown to contain antibiotics, bacteria, and antibiotic resistant genes (McEachran et al 2015). Further, PM less than 10µm in diameter (PM 10 ) has been measured as far as 3.5 km downwind of these facilities (Hiranuma et al 2011), suggesting that animal operations may serve as exposure sources for neighboring communities. A case-control study of methicillin-resistant Staphylococcus aureus (MRSA) in Pennsylvania (Casey et al 2013) found a significant positive association between MRSA and density of swine livestock operations around homes, but no association with dairy/veal livestock operation density.…”
Section: Discussionmentioning
confidence: 99%